2005
DOI: 10.1542/peds.2004-0516
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prenatal Diagnosis, Pregnancy Termination, and Perinatal Mortality of Newborns With Congenital Heart Disease in France, 1983–2000: A Population-Based Evaluation

Abstract: Progress in clinical management, together with policies for increased access to prenatal diagnosis, has resulted in both a substantial increase in the prenatal diagnosis and considerable reductions in early neonatal mortality of CHD in the Parisian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
283
8
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(313 citation statements)
references
References 33 publications
(26 reference statements)
16
283
8
6
Order By: Relevance
“…birth weight <2.5kg and 17% had weight< 1kg. It is reported that congenital malformations contribute highly to prenatal mortality and postnatal physical defects [18][19][20], which is consistent with our observation. WHO reported in 2004 [21] where around 2, 60,000 neonatal deaths (about 7% of all neonatal deaths) were caused by CAs.…”
Section: Discussionsupporting
confidence: 93%
“…birth weight <2.5kg and 17% had weight< 1kg. It is reported that congenital malformations contribute highly to prenatal mortality and postnatal physical defects [18][19][20], which is consistent with our observation. WHO reported in 2004 [21] where around 2, 60,000 neonatal deaths (about 7% of all neonatal deaths) were caused by CAs.…”
Section: Discussionsupporting
confidence: 93%
“…28,30 The highest prenatal detection rates (>93%) were found in CHD with abnormal four-chamber view (hypoplastic left heart syndrome, other univentricular defects and the complex heart defects with atrial isomerism) and exceed previously published series. 5,14,29,30 Hypoplastic right heart syndrome is more frequently overlooked (prenatal detection rate 66.7%), as it may present with a relatively good right ventricular cavity around 20 weeks of gestation. 31 Significant improvements were made in the prenatal detection of several (ductal dependent) outflow tract and aortic arch anomalies that require examination of the outlet views in addition to the four-chamber view.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] About 20-30% of these heart defects are severe, defined as being potentially life threatening and requiring surgery within the first year of life. 2,[5][6][7] Only 10% of CHD cases occur in pregnancies with identifiable risk factors, such as fetal extracardiac malformations. 8,9 The current screening strategy in most western countries is a standard anomaly scan at 20 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Also the number and the subject of publication in a digital database-PubMed, suggests the steady development of prenatal cardiology and different types of registries (Fig.2) at the global level, European and Polish level as well [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Although our National Registry is not perfect one and would need some improvement, still it is a unique organizational "tool" as well as prenatal cardiac defects collection.…”
Section: Discussionmentioning
confidence: 99%